British naval administration in the age of Walpole - Baugh, Daniel A. (Princeton University Press, 1965)
This historical analysis of the problems faced by the British navy during the War of 1739-1748 also sheds light on the character, limitations, and potentialities of eighteenth-century British administration. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.